Operating Drones under Robot Operating System (ROS) - Kho, Daren Ying Cheng (Universiti Teknologi PETRONAS, 2017)
An Unmanned Aerial Vehicle (UAV) is a type of aircraft which can be driven without any pilot, crew or passenger on board. Hence, the size of UAV can be as small as a toy or even as big as a normal aircraft depending on its usage. The term UAV does include both Remotely Piloted Vehicles (RPVs) as well as autonomous drones [1]. Thus, an UAV is widely known as a drone. A drone is normally equipped with lots of sensors such as ultrasonic sensors, gyroscope, accelerometer, proximity sensor, camera and more which allows the drone or the flying robot to be more intelligent while collecting more data for the controller. Basically, the drone will be operated and controlled under Robot Operating System (ROS). Whereas the final aim of this project is to operate multiple drones simultaneously using only one controller.